Recent advances with insulin degludec for the treatment of Type 2 diabetes. Issue 4 (July 2014) - Stokes, Victoria; Gough, Stephen CL
<x xml:space="preserve">Abstract</x> Type 2 diabetes has been referred to as the global epidemic of the 21st century, and is associated with significant morbidity and premature mortality. Estimates suggest that over 50% of people with Type 2 diabetes will at some point need insulin injections to help treat their diabetes. Once daily insulin injections are being increasingly used to initiate insulin in people with Type 2 diabetes and the development of novel, safe, once daily basal insulins with low rates of hypoglycaemia are important to help achieve internationally recommended glycaemic targets for individual patients. Insulin degludec is a novel once daily basal insulin analogue that has been developed for use in people with Type 2 diabetes. A comprehensive drug development program suggests that it can achieve comparable glycaemic control to existing basal insulins but with reduced rates of hypoglycaemia.